Qur'anic Therapy for Happiness: A Psychopathological Analysis and Qur'anic Solutions in Surah Al-Ma'arij Verses 19–35 - Sukandar, Warlan (Indonesian Journal Publisher, 2025)
This article examines the symptoms of human psychopathology as illustrated in Surah Al-Ma‘ārij verses 19–35 and offers a Qur’anic therapeutic approach as a solution to achieve happiness and mental well-being. Using a thematic exegesis approach and content analysis, this study finds that Surah Al-Ma‘ārij reveals three core dimensions of human psychopathology: excessive anxiety (al-halu‘), deep sorrow (al-jazū‘), and miserliness (al-manu‘). These three symptoms reflect spiritual and psychological immaturity, which, in modern psychology, correspond to anxiety disorders, depression, and obsessive-compulsive personality disorder (OCPD). The Qur’an not only identifies these disorders but also provides seven forms of Qur’anic therapy, including consistent prayer (ṣalāh), social compassion, belief in the Day of Judgment, control of desires, and the maintenance of trust and honesty. These findings suggest that integrating Qur’anic values with modern psychological approaches can offer a holistic solution to mental disorders and support the attainment of true happiness.